The entangled state: How state-business relations shaped the German corporate tax regime. (April 2022) - Rademacher, Inga
Contemporary tax research is split into two camps: comparative approaches emphasize continuity and cross-country differences, while the globalization literature stresses similar changes across countries. Counter the continuity thesis, this paper finds that neoliberal dynamics were at play in a case considered largely resilient to such dynamics: German governments implemented a series of corporate tax reforms which radically curbed business taxes and added a short-term and cost-cutting component to investments and corporate finance. While these changes point towards neoliberal change, they were distinct from the trends we see in other economies: crucially, the German reforms did not follow the common trend of reducing taxes for individuals and entailed a particular emphasis on enhancing multinational's access to international capital – but did not liberate financial incomes from tax in general. Based on archival documents from the Bundestagsarchiv, this paper traces the process of German tax reforms and finds that neoliberal dynamics were at play but received a local (export-oriented) colour through processes specific to the German polity. Because consensual institutions granted power to a specific business coalition, radical change was long blocked. Reforms could only be implemented once the state forged a new coalition. Making sense of the mediation of neoliberal dynamics through state institutions can contribute to a better understanding of the variegated nature of neoliberalism.